2023
DOI: 10.1002/alz.12928
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of dementia in India: National and state estimates from a nationwide study

Abstract: Introduction: Prior estimates of dementia prevalence in India were based on samples from selected communities, inadequately representing the national and state populations.Methods: From the Longitudinal Aging Study in India (LASI) we recruited a sample of adults ages 60+ and administered a rich battery of neuropsychological tests and an informant interview in 2018 through 2020. We obtained a clinical consensus rating of dementia status for a subsample (N = 2528), fitted a logistic model for dementia status on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(32 citation statements)
references
References 51 publications
2
27
3
Order By: Relevance
“…We also acknowledge that machine learning is a relatively new approach to estimating dementia prevalence and may generate results that are different to estimates from other statistical methods. Based on the same LASI and LASI-DAD data, a regression-based multiple imputation analysis estimated the dementia prevalence to be 7.4% for adults 60 years or older [39], which is about 1 percentage point lower than this paper's estimate but still higher than prior estimates synthesized from local studies. The reasons for the difference may involve different choices in predictors and statistical models and are worth of further investigation.…”
Section: Discussioncontrasting
confidence: 57%
“…We also acknowledge that machine learning is a relatively new approach to estimating dementia prevalence and may generate results that are different to estimates from other statistical methods. Based on the same LASI and LASI-DAD data, a regression-based multiple imputation analysis estimated the dementia prevalence to be 7.4% for adults 60 years or older [39], which is about 1 percentage point lower than this paper's estimate but still higher than prior estimates synthesized from local studies. The reasons for the difference may involve different choices in predictors and statistical models and are worth of further investigation.…”
Section: Discussioncontrasting
confidence: 57%
“…Therefore, these broad estimates must be followed up with in-depth studies in order to accurately quantify dementia levels in each population. Previous independent reports that assessed dementia rates in locally-conducted community-based cohort studies show prevalence rates in South Asian nations – 8% in Bangladesh [38], 7.4% in India [39], and 4% in Sri Lanka according to a report from 2003 [40].…”
Section: Resultsmentioning
confidence: 99%
“…Such follow-up, focused studies have shown that dementia rates in some South Asian countries have historically been underestimated due to underdiagnoses and underreporting. For example, a recent report showed that there are a few million more cases of dementia in India than previously estimated [39]. This is likely the case for many other LMICs that don’t have dedicated resources to track and monitor the status of aging-associated conditions like dementia.…”
Section: Resultsmentioning
confidence: 99%
“…India is now the most populous nation in the world, with a current population of over 1.4 billion people, and tremendous diversity with respect to sociodemographic characteristics, language, culture, geographical region, rural‐urban residence status, and so forth, which, in turn, could play a significant role in altering the risk and prevalence of dementia. A recent nationwide study that there were substantial inter‐state and rural‐urban differences and that sociodemographic factors, such as age, sex, and education, significantly accounted for these disparities 3 …”
Section: Introductionmentioning
confidence: 99%
“…inter-state and rural-urban differences and that sociodemographic factors, such as age, sex, and education, significantly accounted for these disparities. 3 In addition to the above sociodemographic risk factors, lifestylerelated factors could also impact dementia risk, either directly or indirectly, by influencing the well-known cardiovascular risk factors for dementia. This is particularly relevant in the Indian scenario, wherein the burden of cardiovascular morbidity is accumulating at a disturbing rate.…”
mentioning
confidence: 99%